An In-Vitro Comparison of Effects of Passive Ultrasonic Irrigation with Various Concentrations of Peracetic Acid, Citric Acid, Sodium Hypochlorite, and Ethylene Diamine Tetra Acetic Acid on Removal of Calcium Hydroxide from Root Canals - Manjula Srinivas Pandurangan; Bandlapally Sreenivasa Guptha Anila; Roopadevi Garlapati; Niharika Halder; Mayana Aameena Banu; Lavanya Modala (Journal of Orofacial Sciences)
Introduction: Bacteria play a key role in pulp and periapical disease, making their complete removal essential in endodontic treatment. Calcium hydroxide (Ca(OH)₂) is commonly used as an intracanal medicament due to its antimicrobial properties, but its remnants can hinder sealer adhesion and affect treatment outcomes. This study evaluated the effectiveness of 0.5% peracetic acid (PAA), 10% citric acid (CA), 1% PAA, 3% sodium hypochlorite (NaOCl), and 17% ethylenediamine tetraacetic acid (EDTA) with passive ultrasonic irrigation (PUI), in removing Ca(OH)₂ from root canals. Materials and Method: Sixty teeth that had single roots were chosen and decoronated to set the length of the root at 12 mm. Canals were irrigated, followed by filling up with Ca(OH)₂ after biomechanical preparation. The samples were divided into seven groups: Group 1: Control (positive); Group 2: Control (negative); Group 3: 5 ml of 17% EDTA + PUI; Group 4: 5 ml of 3 % NaOCl+ PUI; Group 5: 5 ml of 0.5% PAA + PUI; Group 6: 5 ml of 1% PAA + PUI; Group 7: 10% CA + PUI. The radicular portions of teeth were split longitudinally, followed by examination beneath a stereomicroscope with a magnification of 50×. Results: The obtained data was statistically analyzed using the Kruskal–Wallis test to find out significant differences between the study groups. Pair-wise comparison for mean scores was done using the Mann–Whitney test. Friedman’s test was used for intra group differences between regions. Small amounts of Ca(OH)₂ residue were observed in the 1% PAA group compared to other irrigants in the coronal, middle, and apical thirds of the root canals, and the difference was statistically significant (p < 0.05). Conclusion: About 1% PAA with PUI was superior in removing Ca(OH)₂ from root canals compared to other irrigants used in the present study.